Upaya Pengembangan Koleksi di Perpustakaan Universitas Nurdin Hamzah - Elva Jelita (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
This article is entitled Collection Development Efforts at the Nurdin Hamzah University Library. By using a descriptive qualitative research method to describe the collection development efforts carried out by librarians at the Nurdin Hamzah University Library Jambi. The primary data in this article is from online interviews with librarians and secondary data is obtained from the analysis of books, journals and related articles. An important activity carried out by libraries is the development of collections because with the development of collections, the needs of users will be fulfilled and the library has better quality and quality. In addition, there is a need for cooperation to meet the information needs of users. From the results and analysis, the Nurdin Hamzah University Library has done a good collection development. Although the Nurdin Hamzah University Library does not yet have a written policy, collection development activities are also carried out by the library such as community or user analysis, policies on collection development, selection of library materials, procurement of library materials, weeding of library materials and evaluation of collection development are often carried out annually at the library. Nurdin Hamzah University.